2005
DOI: 10.1614/wt-03-248r
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Drift Control Agents to Reduce Short Distance Movement and Effect on Herbicide Performance1

Abstract: Spray drift to unintended areas is more of a concern as applications of nonselective herbicides associated with herbicide-resistant crops and the proximity of residential land to agricultural land increase. This research evaluated the benefit of three commercial drift control agents for effectiveness in reducing drift in 19 to 24 km/h wind and their potential effect on weed control. The drift control agents were added to a spray mixture of glyphosate at 0.8 kg ae/ha applied in 140 L/ ha and applied with either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Fietsam et al (2004) found that a polyacrylamide-and polysaccharide-based DCA reduced total drift by 13% and 18%, respectively. Similar to our findings, Vangessel et al (2005) found that the addition of DCAs to flood or flat-fan nozzles did not reduce spray drift or injury to sorghum.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Fietsam et al (2004) found that a polyacrylamide-and polysaccharide-based DCA reduced total drift by 13% and 18%, respectively. Similar to our findings, Vangessel et al (2005) found that the addition of DCAs to flood or flat-fan nozzles did not reduce spray drift or injury to sorghum.…”
Section: Resultssupporting
confidence: 90%
“…This lack of change in D V0.1 values is probably the reason there was no difference in D L or D I distances for the two pressures. Although detectable drift would have been greater if the water-sensitive cards had been placed above the soil surface (Vangessel and Johnson 2005), the relative differences among nozzles are not expected to have been different.…”
Section: Resultsmentioning
confidence: 99%
“…Drift control agents can also impact the size of droplets by altering the viscosity of the spray solution through reducing the liquid's ability to stretch and separate into small droplets (VanGessel and Johnson 2005). When asked how frequently applicators added drift control agents to the solution, 74% of commercial and 48% of noncommercial applicators indicated that they use drift control agents ≥50% of the time (Table 4).…”
Section: Current Herbicide Application Practicesmentioning
confidence: 99%
“…Many factors that can contribute to herbicides moving away from target plants and onto nontarget plants, such as physical drift of herbicide droplets and contamination of improperly cleaned spray tanks, can be managed by the applicator (Vangessel and Johnson 2005).…”
mentioning
confidence: 99%
“…Drift control agents modify spray characteristics to reduce spray drift, usually by minimizing small droplet formation. They are generally polyacrylamide or polyvinyl polymers [52].…”
Section: Drift Control Agentsmentioning
confidence: 99%